Battery manufacturing method

By using a hot weld layer and an adhesive layer during the manufacturing process of the battery, and using an adsorption mechanism to keep the laminated body from peeling, the problem of internal stress collapse and fitting position deviation when the electrode is formed on the surface of the current collector is solved, and the stability and performance of the battery manufacturing are improved.

CN119605008AInactive Publication Date: 2025-03-11FUJIFILM CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380056665.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-28
Filing Date
2023-07-25
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the process of manufacturing a battery of thick film electrodes by roll-to-roll, the electrode is prone to collapse due to internal stress when the current collector surface is formed, resulting in a deflection of the bonding position and may cause a short circuit.

Method used

By providing a hot welding layer and an adhesive layer on the surface of the stage, and forming a current collector and an electrode laminate on the surface, an adsorption mechanism is used to keep the laminate from peeling, reducing the application of external force on the electrode, thereby suppressing electrode collapse and offset of the bonding position.

Benefits of technology

It effectively suppresses the collapse of the electrode from the current collector and the offset of the fitting position, reduces the possibility of short circuits, and improves the manufacturing stability and performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119605008A_ABST
    Figure CN119605008A_ABST
Patent Text Reader

Abstract

Provided is a method for manufacturing a battery, comprising: a step for obtaining a first laminate by forming a positive electrode on the surface of a first current collector on a first stage, the surface of which is provided with the first current collector; forming a negative electrode on the surface of a second current collector of a second stage having the second current collector provided on the surface thereof to obtain a second laminate; and laminating the first laminate, the second laminate, and a separator to obtain a laminate provided with the first stage, a battery provided with the first current collector, the positive electrode, the separator, the negative electrode, and the second current collector, and the second stage in this order.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for manufacturing a battery. Background Art

[0002] In recent years, research on the development of semi-solid-state batteries or all-solid-state batteries is underway.

[0003] A semi-solid-state battery and an all-solid-state battery (hereinafter also collectively referred to as a battery) have a structure including a first current collector, a positive electrode, a separator, a negative electrode, and a second current collector in this order.

[0004] In recent years, for the purpose of reducing costs, studies have been conducted on increasing the thickness of the positive electrode and the negative electrode (hereinafter also collectively referred to as electrodes) to reduce the number of parts. Summary of the invention

[0005] Technical issues to be solved by the invention

[0006] From the viewpoint of manufacturing efficiency, a roll-to-roll method is often used as a method for manufacturing batteries (for example, refer to Japanese Unexamined Patent Application Publication No. 2021-530829).

[0007] The present inventors have found that when a battery having a thick electrode is produced by a roll-to-roll method, when the electrode is formed on the surface of a current collector being transported, external force is applied to the electrode, causing internal stress in the electrode.

[0008] Generally, the electrode adheres to the collector by van der Waals force without using an adhesive or the like. Therefore, the following insight is obtained: due to the above-mentioned internal stress, the electrode collapses from the collector, and the bonding position of the collector formed with the positive electrode and the collector formed with the negative electrode may be offset. In addition, when the bonding position is offset, lithium or the like may be precipitated from the electrode, and the separator may be destroyed, resulting in a short circuit.

[0009] An embodiment of the present invention aims to provide a method for manufacturing a battery that can suppress collapse of an electrode from a current collector and can suppress deviation in the bonding position between a current collector having a positive electrode and a current collector having a negative electrode.

[0010] Means for solving technical problems

[0011] The specific methods used to solve the problem are as follows.

[0012] <1> A method for manufacturing a battery, comprising the following steps:

[0013] A first stack is obtained by forming a positive electrode on the surface of the first current collector of a first stage having a first current collector disposed on the surface thereof;

[0014] A negative electrode is formed on the surface of the second current collector of the second stage having the second current collector disposed on the surface thereof, thereby obtaining a second stacked body; and

[0015] The first stack, the second stack and the separator are stacked to obtain a stack including the first stage, a battery including the first current collector, the positive electrode, the separator, the negative electrode and the second current collector, and the second stage in this order.

[0016] <2> The method for manufacturing a battery according to <1> above, wherein:

[0017] The positive electrode and the negative electrode are formed of a composition containing an active material and a conductive auxiliary agent.

[0018] The solid content of the composition is 30% to 60% by volume relative to the total volume of the composition.

[0019] <3> The method for manufacturing a battery according to <1> or <2> above, wherein:

[0020] The first stage and the second stage have a suction mechanism.

[0021] <4> The method for producing a battery according to any one of <1> to <3> above, wherein:

[0022] A heat-sealing layer and the first current collector are sequentially provided on the surface of the first stage, and a heat-sealing layer and the second current collector are sequentially provided on the surface of the second stage.

[0023] <5> The method for producing a battery according to any one of <1> to <4> above, wherein:

[0024] The first stack, the second stack, and the separator are stacked by the following steps:

[0025] The end of the diaphragm is held by a holding member;

[0026] bringing one surface of the separator into contact with the positive electrode of the first stack or the negative electrode of the second stack;

[0027] Opening the separator from the holding member and placing the separator on the surface of the positive electrode of the first stack or the negative electrode of the second stack;

[0028] The positive electrode of the first stack or the negative electrode of the second stack is placed on the other surface of the separator.

[0029] Effects of the Invention

[0030] According to one embodiment of the present invention, a method for manufacturing a battery can be provided that can suppress collapse of electrodes from current collectors and can suppress deviation in the bonding position between current collectors having positive electrodes and current collectors having negative electrodes. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a battery of the present invention.

[0032] Figure 2 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a battery of the present invention.

[0033] Figure 3 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a battery of the present invention.

[0034] Figure 4 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a battery of the present invention.

[0035] Figure 5 This is a schematic cross-sectional view for explaining one embodiment of a method for manufacturing a battery of the present invention.

[0036] Figure 6 This is a schematic cross-sectional view for explaining one embodiment of a method for laminating separators.

[0037] Figure 7 This is a plan view for explaining the formation of the first current collector on the surface of the heat-sealing layer in Example 1.

[0038] Figure 8 This is a top view for explaining the formation of a positive electrode on the surface of the first current collector in Example 1.

[0039] Fig. 9 This is a plan view for explaining the formation of a second current collector on the surface of the heat-sealed layer in Example 1.

[0040] Fig.10 This is a top view for explaining the formation of a negative electrode on the surface of the second current collector in Example 1. DETAILED DESCRIPTION

[0041] Hereinafter, embodiments of the present invention will be described with reference to the accompanying drawings. The present invention is not limited to the following embodiments and can be implemented with appropriate changes within the scope of the purpose of the present invention. Constituent elements represented by the same symbols in the drawings refer to the same constituent elements. The description of the constituent elements and symbols repeated in the drawings may sometimes be omitted. The ratio of the dimensions in the drawings does not necessarily represent the ratio of the actual dimensions.

[0042] In the present invention, the numerical range represented by "to" refers to a range including the numerical values ​​recorded before and after "to" as the lower limit and the upper limit. In the numerical range recorded in stages in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other stages. In addition, in the numerical range recorded in the present invention, the upper limit or lower limit recorded in a certain numerical range can be replaced by the value shown in the embodiment.

[0043] In the present invention, the term "process" includes not only an independent process but also a process that cannot be clearly distinguished from other processes as long as the intended purpose of the process can be achieved.

[0044] In the present invention, when a plurality of substances corresponding to each component are present in the composition, the amount of each component in the composition refers to the total amount of the plurality of substances present in the composition unless otherwise specified.

[0045] In the present invention, a combination of two or more preferred aspects or configurations is a more preferred aspect or configuration.

[0046] In the present invention, the "solid content" refers to a component that is solid at 25°C and 1 atmosphere, and the "liquid content" refers to a component that is liquid at 25°C and 1 atmosphere.

[0047] In the present invention, when the embodiments are described with reference to the drawings, the structure of the embodiments is not limited to the structure shown in the drawings. In addition, the sizes of the components in the drawings are conceptual, and the relative relationship between the sizes of the components is not limited thereto.

[0048] [Battery manufacturing method]

[0049] The manufacturing method of the battery of the present invention comprises the following steps:

[0050] A positive electrode is formed on the surface of a first current collector of a first stage having a first current collector disposed on the surface thereof, thereby obtaining a first stacked body;

[0051] forming a negative electrode on the surface of the second current collector of the second stage having the second current collector disposed on the surface thereof, thereby obtaining a second stacked body; and

[0052] The first stack, the second stack, and the separator are stacked to obtain a stack including a first stage, a battery including a first current collector, a positive electrode, a separator, a negative electrode, and a second current collector, and a second stage in this order.

[0053] According to the manufacturing method of the battery of the present invention, the collapse of the electrode from the collector can be suppressed (hereinafter, the collapse of the electrode from the collector is also referred to as "electrode collapse"), and the deviation of the bonding position between the collector forming the positive electrode and the collector forming the negative electrode can be suppressed (hereinafter, the deviation of the bonding position between the collector forming the positive electrode and the collector forming the negative electrode is also referred to as "deviation of the bonding position".).

[0054] The reason why the above effects are exerted is not clear, but is presumed as follows.

[0055] In the battery manufacturing method of the present invention, a battery is manufactured by stacking a first stack having a first current collector and a positive electrode placed on the surface of a first stage and a second stack having a second current collector and a negative electrode placed on the surface of a second stage with a separator interposed therebetween without being peeled off from the stages.

[0056] In the present invention, as described above, the battery including the first current collector, the positive electrode, the separator, the negative electrode, and the second current collector in sequence can be manufactured in a monolithic manner without being peeled off from the stage, so that the external force applied to the electrodes can be reduced during the manufacture of the battery. Therefore, it is presumed that the collapse of the electrodes and the displacement of the bonding position can be suppressed.

[0057] (Step of Obtaining the First Laminated Body and the Second Laminated Body)

[0058] The manufacturing method of the battery of the present invention includes the following steps: forming a positive electrode on the surface of a first current collector of a first carrier having a first current collector disposed on its surface to obtain a first stack; and forming a negative electrode on the surface of a second current collector of a second carrier having a second current collector disposed on its surface to obtain a second stack.

[0059] Here, the first stack refers to a stack including a first current collector and a positive electrode, and the second stack refers to a stack including a second current collector and a negative electrode.

[0060] The method of forming the positive electrode on the surface of the first current collector and the method of forming the negative electrode on the surface of the second current collector are not particularly limited, and can be performed by conventionally known methods.

[0061] For example, a positive electrode or a negative electrode can be formed by applying a composition including a positive electrode active material or a negative electrode active material and a conductive auxiliary agent onto the surface of a first current collector or a second current collector.

[0062] The method for arranging the first current collector on the surface of the first stage and the method for arranging the second current collector on the surface of the second stage are not particularly limited, and can be performed by conventionally known methods.

[0063] For example, when a heat-sealing layer is provided on the surface of the first stage, an adhesive layer is formed on the surface of the heat-sealing layer, and an aluminum foil is arranged as a current collector on the surface of the adhesive layer, thereby arranging the first current collector on the surface of the first stage.

[0064] The method for forming the heat-sealed layer is not particularly limited, and the heat-sealed layer can be formed by placing a resin film or the like on the surface of the first stage.

[0065] Furthermore, as described later, when the first stage and the second stage are provided with a suction mechanism, the heat-sealed layer can be held on the surfaces of the first stage and the second stage by the suction mechanism.

[0066] The method for forming the adhesive layer is not particularly limited, and examples thereof include a method of applying an adhesive or the like on the surface of the heat-sealing layer, a method of disposing an adhesive film or the like, and the like.

[0067] -1st stage and 2nd stage-

[0068] A first current collector is provided on the surface of the first stage, and a second current collector is provided on the surface of the second stage.

[0069] A heat-sealing layer and the first current collector may be provided in this order on the surface of the first stage. Also, the heat-sealing layer, the adhesive layer and the first current collector may be provided in this order on the surface of the first stage.

[0070] A heat-sealing layer and the second current collector may be provided in sequence on the surface of the second stage. Also, the heat-sealing layer, the adhesive layer and the second current collector may be provided in sequence on the surface of the second stage.

[0071] In addition, the first current collector, the second current collector, and the like described above are preferably provided so as to be removable from the first stage and the second stage.

[0072] The material constituting the first stage and the second stage (hereinafter also collectively referred to as the stage) is not particularly limited, and examples thereof include aluminum, stainless steel, and phenolic plastic.

[0073] The stage may be provided with an adsorption mechanism.

[0074] There is no particular limitation on the adsorption mechanism as long as it can function to adsorb the target component (thermal welding layer, adhesive layer, current collector, electrode, etc.) on the stage surface. The adsorption mechanism is, for example, composed of a plurality of holes provided on the stage surface and an air suction pipe connected to the stage and a vacuum pump. The air inside the hole provided on the stage surface is sucked from the air suction pipe to set the inside of the hole to a decompressed state, thereby improving the retention of the thermal welding layer, adhesive layer, current collector, electrode, etc. on the stage surface.

[0075] In addition, the adsorption mechanism can stop holding the collector, etc. when the suction from the suction pipe is stopped, or maintain the reduced pressure state inside the hole set on the stage surface and maintain the collector, etc. for a certain period of time.

[0076] The thickness of the stage is not particularly limited, and can be set to 1 mm to 50 mm, for example, from the viewpoint of transportability.

[0077] -1st current collector-

[0078] The first current collector may contain a material known in the art for use in positive electrode current collectors. The first current collector preferably contains one or more metals selected from the group consisting of aluminum, aluminum alloys, stainless steel, nickel, and titanium, and more preferably contains one or more metals selected from the group consisting of aluminum and aluminum alloys.

[0079] Furthermore, the first current collector may have a coating layer including one or more of carbon, nickel, titanium, silver, gold, platinum, and vanadium oxide on its surface.

[0080] From the viewpoint of transportability and the like, the thickness of the first current collector is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more.

[0081] From the viewpoint of flexibility and lightness, the thickness is preferably 100 μm or less, more preferably 70 μm or less, and even more preferably 50 μm or less.

[0082] - Second collector -

[0083] The second current collector may contain a material known in the art that is contained in the negative electrode current collector. The second current collector preferably contains one or more metals selected from the group consisting of aluminum, copper, copper alloys, stainless steel, nickel, and titanium, and more preferably contains one or more metals selected from the group consisting of aluminum, copper, copper alloys, and stainless steel.

[0084] Furthermore, the second current collector may have a coating layer including one or more of carbon, nickel, titanium, silver, gold, platinum, and vanadium oxide on its surface.

[0085] From the viewpoint of transportability and the like, the thickness of the second current collector is preferably 3 μm or more, more preferably 5 μm or more, and particularly preferably 10 μm or more.

[0086] From the viewpoint of flexibility and lightness, the thickness is preferably 100 μm or less, more preferably 70 μm or less, and particularly preferably 50 μm or less.

[0087] - Positive and negative electrodes -

[0088] The positive electrode and the negative electrode (hereinafter, also collectively referred to as electrodes) are composed of a composition containing an active material and a conductive auxiliary agent.

[0089] The active material is preferably a material that can reversibly absorb and release lithium ions.

[0090] From the viewpoint of improving the volume energy density, the positive electrode and the negative electrode are formed of a composition comprising an active material and a conductive aid, and the solid content relative to the total volume of the composition (i.e., the total volume of the electrode) only needs to be 30% by volume or more, preferably 30% to 60% by volume, more preferably 35% to 55% by volume, and even more preferably 40% to 50% by volume.

[0091] Examples of active materials that can be used for the positive electrode (hereinafter referred to as positive electrode active materials) include transition metal oxides and elements that can form a complex with lithium (for example, sulfur). Among the above, the positive electrode active material is preferably a transition metal oxide.

[0092] The transition metal oxide is preferably a transition metal oxide containing at least one transition metal element (hereinafter referred to as “element Ma”) selected from the group consisting of Co (cobalt), Ni (nickel), Fe (iron), Mn (manganese), Cu (copper) and V (vanadium).

[0093] When the transition metal oxide contains Li and the element Ma, the molar ratio of Li to Ma (Li / Ma) is preferably 0.3 to 2.2.

[0094] Furthermore, the transition metal oxide may contain at least one transition metal element (hereinafter referred to as "element Mb") selected from the group consisting of Group 1 elements other than lithium, Group 2 elements, Al (aluminum), Ga (gallium), In (indium), Ge (germanium), Sn (tin), Pb (lead), Sb (antimony), Bi (bismuth), Si (silicon), P (phosphorus) and B (boron).

[0095] The content of the element Mb is preferably 0 mol % to 30 mol % relative to the amount of substance of the element Ma.

[0096] Examples of the transition metal oxide include transition metal oxides having a layered rock salt structure, transition metal oxides having a spinel structure, lithium-containing transition metal phosphate compounds, lithium-containing transition metal halophosphate compounds, and lithium-containing transition metal silicate compounds.

[0097] Examples of transition metal oxides having a layered rock salt structure include LiCoO2 (lithium cobalt oxide [LCO]), LiNi2O2 (lithium nickel oxide), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]), LiNi 1 / 3 Co1 / 3 Mn 1 / 3 O2 (lithium nickel manganese cobalt oxide [NMC]), LiNi 0.5 Mn 0.5 O2 (lithium manganese nickel oxide), etc.

[0098] Examples of transition metal oxides having a spinel structure include LiCoMnO4, Li2FeMn3O8, Li2CuMn3O8, Li2CrMn3O8, and Li2NiMn3O8.

[0099] As lithium-containing transition metal phosphate compounds, there can be mentioned olivine-type iron phosphates (for example, LiFePO4 and Li3Fe2(PO4)3), pyrophosphate iron salts (for example, LiFeP2O7), cobalt phosphate salts (for example, LiCoPO4), monoclinic NASICON-type vanadium phosphate salts (for example, Li3V2(PO4)3 (lithium vanadium phosphate)), etc.

[0100] Examples of lithium-containing transition metal halophosphate compounds include iron fluorophosphates (eg, Li2FePO4F), manganese fluorophosphates (eg, Li2MnPO4F), and cobalt fluorophosphates (eg, Li2CoPO4F).

[0101] Examples of lithium-containing transition metal silicate compounds include Li2FeSiO4, Li2MnSiO4, and Li2CoSiO4.

[0102] The transition metal oxide is preferably a transition metal oxide having a layered rock salt structure, and more preferably selected from LiCoO2 (lithium cobalt oxide [LCO]), LiNi 0.85 Co 0.10 Al 0.05 O2 (nickel cobalt aluminum oxide [NCA]) and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one compound selected from the group consisting of O2 (lithium nickel manganese cobalt oxide [NMC]).

[0103] The positive electrode active material may be a commercially available product or a synthetic product produced by a known method (eg, calcination method). For example, the positive electrode active material obtained by calcination method may be washed with water, an acidic aqueous solution, an alkaline aqueous solution or an organic solvent.

[0104] Furthermore, the positive electrode active material may have a carbon coating on its surface.

[0105] The shape of the positive electrode active material is not limited, but is preferably in the form of particles from the viewpoint of handleability.

[0106] The volume average particle size of the positive electrode active material is not limited, and can be, for example, 0.1 μm to 50 μm. The volume average particle size of the positive electrode active material is preferably 0.3 μm to 40 μm, and more preferably 0.5 μm to 30 μm.

[0107] The volume average particle size of the positive electrode active material is 0.3 μm or more, so that the positive electrode can be easily formed and the splashing of the material constituting the positive electrode can be suppressed during operation. The volume average particle size of the positive electrode active material is 40 μm or less, so that the thickness of the battery can be easily adjusted and the generation of voids during the molding process can be suppressed.

[0108] The volume average particle size of the positive electrode active material is measured by the following method.

[0109] A dispersion containing 0.1% by mass of the positive electrode active material is prepared by mixing the positive electrode active material with a solvent (e.g., heptane, octane, toluene or xylene). The dispersion irradiated with 1 kHz ultrasonic waves for 10 minutes is set as a measurement sample. Using a laser diffraction / scattering particle size distribution measuring device (e.g., LA-920 manufactured by HORIBA, Ltd.) and at a temperature of 25°C, 50 data readings are performed to determine the volume average particle size. A quartz colorimetric cell is used in the measuring cell. The above measurement is performed using 5 samples, and the average of the measured values ​​is set as the volume average particle size of the positive electrode active material. For other detailed conditions, refer to "JIS Z 8828:2013" as needed.

[0110] As a method for adjusting the particle size of the positive electrode active material, for example, there can be mentioned a method using a pulverizer, a disintegrator, or a classifier. Also, as a method for adjusting the particle size of the positive electrode active material, a known grinding method can be applied.

[0111] The composition may contain a single positive electrode active material, or may contain two or more positive electrode active materials.

[0112] Furthermore, even when the composition contains one type of positive electrode active material, positive electrode active materials having different particle sizes may be used in combination.

[0113] The content of the positive electrode active material relative to the total volume of the composition constituting the positive electrode may be 30% by volume or more, preferably 30% to 60% by volume, more preferably 35% to 55% by volume, and even more preferably 40% to 50% by volume.

[0114] The surface of the positive electrode active material may be coated with a surface coating agent. As the surface coating agent, for example, a metal oxide containing Ti, Nb, Ta, W, Zr, Si or Li can be cited. As the above-mentioned metal oxide, for example, titanate spinel, tantalum oxide, niobium oxide and lithium niobate compounds can be cited.

[0115] Examples of active materials that can be used for the negative electrode (hereinafter referred to as negative electrode active materials) include carbonaceous materials, metal oxides (e.g., tin oxide), silicon oxide, metal composite oxides, lithium monomers, lithium alloys (e.g., lithium aluminum alloys), and metals that can form alloys with lithium (e.g., Sn, Si, In).

[0116] Among the above, the negative electrode active material is preferably a carbonaceous material or a lithium composite oxide from the viewpoint of reliability.

[0117] Examples of carbonaceous materials include petroleum pitch, carbon black (e.g., acetylene black), graphite (e.g., natural graphite, artificial graphite (e.g., vapor-grown graphite)), hard carbon, and materials made of calcined synthetic resins (e.g., polyacrylonitrile (PAN), furfuryl alcohol resin).

[0118] As the carbonaceous material, carbon fibers (polyacrylonitrile carbon fibers, cellulose carbon fibers, pitch carbon fibers, vapor grown carbon fibers, dehydrated PVA (polyvinyl alcohol) carbon fibers, lignin carbon fibers, glassy carbon fibers, activated carbon fibers, etc.) can be used.

[0119] Examples of graphite include mesophase microspheres, graphite whiskers, and flat graphite.

[0120] In the present invention, "flat plate shape" means a shape having two main planes facing in opposite directions.

[0121] As the metal composite oxide, a metal composite oxide capable of occluding and releasing lithium is preferred.

[0122] From the viewpoint of high current density charge and discharge characteristics, the metal composite oxide capable of occluding and releasing lithium preferably contains at least one element selected from the group consisting of titanium and lithium.

[0123] The metal oxide and the metal composite oxide are particularly preferably amorphous oxides.

[0124] The metal oxide and the metal composite oxide are also preferably chalcogenides. Chalcogenides are reaction products between metal elements and elements of Group 16 in the periodic table.

[0125] Among the compound group consisting of amorphous oxides and chalcogenides, amorphous oxides and chalcogenides of semimetallic elements are also preferred, and oxides and chalcogenides of at least one element selected from the group consisting of elements of Groups 13 to 15 in the periodic table, Al, Ga, Si, Sn, Ge, Pb, Sb and Bi are more preferred.

[0126] The negative electrode active material preferably further contains titanium. The volume change during the storage and release of lithium ions is small, so the rapid charge and discharge characteristics are excellent, and from the perspective of suppressing electrode degradation and increasing the life of the lithium ion secondary battery, the negative electrode active material containing titanium is preferably Li4Ti5O 12 (lithium titanate [LTO]).

[0127] The negative electrode active material may be a commercially available product or a synthetic product produced by a known method (eg, calcination method). For example, the negative electrode active material obtained by calcination method may be washed with water, an acidic aqueous solution, an alkaline aqueous solution or an organic solvent.

[0128] The shape of the negative electrode active material is not limited, but is preferably in the form of particles from the viewpoint of easy handling and easy control of uniformity during mass production.

[0129] The volume average particle size of the negative electrode active material is preferably 0.1 μm to 60 μm, more preferably 0.3 μm to 50 μm, and particularly preferably 0.5 μm to 40 μm.

[0130] The volume average particle size of the negative electrode active material is measured by a method based on the method for measuring the volume average particle size of the positive electrode active material described above.

[0131] As a method of adjusting the particle size of the negative electrode active material, there is mentioned, for example, a method of using a pulverizer or a classifier.

[0132] The composition contained in the negative electrode may contain a single type of negative electrode active material, or may contain two or more types of negative electrode active materials.

[0133] The content of the negative electrode active material relative to the total volume of the composition constituting the negative electrode may be 30% by volume or more, preferably 30% to 60% by volume, more preferably 35% to 57% by volume, and even more preferably 45% to 55% by volume.

[0134] The surface of the negative electrode active material may be coated with the above-mentioned surface coating agent.

[0135] From the viewpoint of improving electron conductivity, the composition preferably contains a conductive auxiliary agent. The conductive auxiliary agent is not limited, and a known conductive auxiliary agent can be used.

[0136] The conductive auxiliary agent is contained in the solid component.

[0137] As conductive aids, there can be mentioned graphite (e.g., natural graphite, artificial graphite), carbon black (e.g., acetylene black, Ketjen black, furnace black), amorphous carbon (e.g., needle coke), carbon fiber (e.g., vapor grown carbon fiber), other carbonaceous materials (e.g., graphene, fullerene), metal powder (e.g., copper powder, nickel powder), metal fiber (e.g., copper fiber, nickel fiber) and conductive polymers (e.g., polyaniline, polypyrrole, polythiophene, polyacetylene, polyphenylene derivatives, etc.), etc.

[0138] The above composition may contain a single conductive aid or two or more conductive aids.

[0139] When the composition contains a conductive aid, from the viewpoint of improving electron conductivity, the content of the conductive aid is preferably 0.05 to 5 volume %, more preferably 0.1 to 4 volume %, and even more preferably 0.5 to 3 volume % relative to the total volume of the composition.

[0140] From the viewpoint of improving battery performance (discharge capacity, output characteristics, etc.), the composition may contain an inorganic solid electrolyte.

[0141] Here, the “solid electrolyte” refers to a solid electrolyte that can move ions inside.

[0142] The inorganic solid electrolyte is contained in the solid component.

[0143] Inorganic solid electrolytes are not electrolytes containing organic matter as the main ion conductive material, and therefore are clearly distinguished from organic solid electrolytes (for example, polymer electrolytes represented by polyethylene oxide (PEO) and organic electrolyte salts represented by lithium bis(trifluoromethanesulfonyl)imide (LiTFSI)).

[0144] In addition, inorganic solid electrolytes are solid in a stable state and therefore do not dissociate or liberate into cations or anions. Therefore, they are clearly distinguished from inorganic electrolyte salts (e.g., LiPF6, LiBF4, lithium bis(fluorosulfonyl)imide (LiFSI), LiCl) that dissociate or liberate into cations or anions in electrolytes and polymers.

[0145] The inorganic solid electrolyte is not limited as long as it has ion conductivity of a metal element belonging to Group 1 or Group 2 of the periodic table, but generally does not have electron conductivity.

[0146] In the case where the battery is used as a lithium ion battery, the inorganic solid electrolyte preferably has ion conductivity for lithium ions.

[0147] Examples of the inorganic solid electrolyte include sulfide-based inorganic solid electrolytes and oxide-based inorganic solid electrolytes. Among the above, the inorganic solid electrolyte is preferably a sulfide-based inorganic solid electrolyte from the viewpoint of forming a good interface between the active material and the inorganic solid electrolyte.

[0148] The inorganic solid electrolyte is preferably in a particle form.

[0149] The volume average particle size of the inorganic solid electrolyte is preferably 0.01 μm or more, and more preferably 0.1 μm or more. The upper limit of the volume average particle size of the inorganic solid electrolyte is preferably 100 μm or less, and more preferably 50 μm or less.

[0150] The volume average particle size of the inorganic solid electrolyte is measured by a method based on the method for measuring the volume average particle size of the positive electrode active material described above.

[0151] The composition may contain a single inorganic solid electrolyte or may contain two or more inorganic solid electrolytes.

[0152] When the composition contains an inorganic solid electrolyte, the content of the inorganic solid electrolyte relative to the total volume of the composition is more preferably 25 to 35 volume % from the viewpoint of reducing interface resistance and maintaining battery characteristics (eg, improving cycle characteristics).

[0153] The composition may comprise an electrolyte.

[0154] The electrolyte is contained in the liquid component.

[0155] The electrolyte is not limited, and a known electrolyte can be used. For example, an electrolyte containing an electrolyte and a solvent can be cited. As a specific electrolyte, for example, an electrolyte containing a lithium salt compound as an electrolyte and a carbonate compound as a solvent can be cited.

[0156] As the lithium salt compound, for example, lithium hexafluorophosphate can be mentioned. The electrolyte solution may contain a single lithium salt compound, or may contain two or more lithium salt compounds.

[0157] As carbonate compounds, for example, chain carbonate compounds such as ethyl methyl carbonate (also referred to as EMC), dimethyl carbonate (also referred to as DMC), diethyl carbonate (DEC) and cyclic carbonate compounds such as ethylene carbonate (also referred to as EC) and propylene carbonate (also referred to as PC) can be cited. The electrolyte can include a single carbonate compound, can include two or more carbonate compounds, and can also use more than one chain carbonate compound and more than one cyclic carbonate compound simultaneously.

[0158] Examples of the electrolyte contained in the electrolytic solution include the materials described in the above section "inorganic solid electrolyte".

[0159] As a component of the electrolytic solution, for example, an ionic liquid can be used. The ionic liquid can be used as an electrolyte or as a solvent.

[0160] The content of the electrolyte relative to the total volume of the composition is preferably 70% by volume or less, preferably 60% by volume or less, and more preferably 55% by volume or less. The content of the electrolyte in the composition is 70% by volume or less, thereby suppressing electrolyte seepage when the composition is molded.

[0161] The lower limit of the content of the electrolyte solution in the composition is not limited, and may be 0 volume % or more, or may exceed 0 volume %.

[0162] The composition may contain, as a liquid component, a solvent other than the solvent contained as a component of the electrolytic solution (hereinafter, also simply referred to as a "solvent").

[0163] Examples of the solvent include alcohol compound solvents, ether compound solvents, amide compound solvents, amino compound solvents, ketone compound solvents, aromatic compound solvents, aliphatic compound solvents, and nitrile compound solvents.

[0164] The boiling point of the solvent is preferably 50° C. or higher, more preferably 70° C. or higher, at normal pressure (ie, 1 atmosphere). The upper limit of the boiling point of the solvent is preferably 250° C. or lower, more preferably 220° C. or lower, at normal pressure (ie, 1 atmosphere).

[0165] The composition may contain a single solvent or two or more solvents.

[0166] The content of the liquid component (ie, the electrolyte solution and the solvent) relative to the total volume of the composition is preferably 70% by volume or less, preferably 60% by volume or less, and more preferably 55% by volume or less.

[0167] The content of the liquid component in the composition is 70% by volume or less, thereby preventing the liquid component from seeping out when the composition is molded. Furthermore, when the liquid component contains a solvent, degradation of battery performance can be prevented.

[0168] The lower limit of the content of the liquid component in the composition is not limited, and it may be 0 volume % or more, or may exceed 0 volume %.

[0169] In addition, the liquid component in the composition, that is, the component in the composition that is liquid at 25° C., is preferably liquid even at -10° C., and is preferably liquid even at -20° C. That is, the component in the composition that is liquid at 25° C. is preferably a component that does not solidify at -10° C., and is preferably a component that does not solidify at -20° C.

[0170] The composition may contain additives such as a binder, a pigment, a dye, a UV absorber, a light stabilizer, an antioxidant, and a thickener.

[0171] From the viewpoint of reducing costs and suppressing an excessive increase in internal resistance, the thickness of the electrode is preferably 50 μm to 700 μm, and more preferably 100 μm to 650 μm.

[0172] -Thermal welding layer-

[0173] By providing a heat-sealing layer on the stage surface, a battery having a structure sealed by heat-sealing the heat-sealing layer on the first current collector side and the heat-sealing layer on the second current collector side can be manufactured.

[0174] The heat-sealing layer may contain a thermoplastic resin. Examples of the thermoplastic resin include polyethylene terephthalate (PET), polypropylene (PP), polyethylene (PE), cyclic olefin polymers, triacetyl cellulose (TAC), polyimide (PI), polyamide (PA), ethylene-vinyl acetate copolymer (EVA), and ethylene-methyl methacrylate copolymer (EMMA).

[0175] The content of the thermoplastic resin relative to the total mass of the heat-sealing layer is not particularly limited, and may be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 100% by mass.

[0176] The heat-sealing layer may contain the above-mentioned additives.

[0177] The thickness of the heat-sealing layer is not particularly limited, and can be, for example, 3 μm to 25 μm.

[0178] - Adhesive layer -

[0179] The adhesive layer may contain the above-mentioned thermoplastic resin. By providing the adhesive layer on the surface of the heat-sealing layer, the adhesion between the heat-sealing layer and the current collector can be improved.

[0180] The content of the thermoplastic resin relative to the total mass of the adhesive layer is not particularly limited, and may be 50% by mass or more, 70% by mass or more, 90% by mass or more, or 100% by mass.

[0181] The adhesive layer may contain the above-mentioned additives.

[0182] The thickness of the adhesive layer is not particularly limited, and can be 0.1 μm to 10 μm.

[0183] [Step of Obtaining Laminated Body]

[0184] The method for manufacturing a battery of the present invention includes the steps of stacking a first stack, a second stack and a separator to obtain a battery having a first stage, a first stage, a positive electrode, a separator, a negative electrode and a second stage, and a stack having a second stage.

[0185] The method of laminating the first stack, the second stack, and the separator is not particularly limited, and can be performed by a conventionally known method.

[0186] For example, there is a method in which a separator is sandwiched between the positive electrode of the first stack and the negative electrode of the second stack, and a pressure roll is used to form a stack.

[0187] The lamination of the first laminate, the second laminate, and the separator is preferably performed by the following steps:

[0188] The end of the separator is held by a holding member so that one surface of the separator is in contact with the positive electrode of the first stack or the negative electrode of the second stack;

[0189] Opening the separator from the holding member and placing the separator on the surface of the positive electrode of the first stack or the negative electrode of the second stack;

[0190] The positive electrode of the first stack or the negative electrode of the second stack is placed on the other surface of the separator.

[0191] According to the above lamination method, the positive electrode or the negative electrode can be laminated from the center portion toward the end portion of the separator, and air accumulation between the separator and the positive electrode or the negative electrode can be suppressed.

[0192] like Figure 6 As shown, the end of the diaphragm 30 is held by a holding member 60. The method of holding the diaphragm by the holding member is not particularly limited, and a method such as providing an adsorption mechanism on the holding member can be mentioned.

[0193] From the viewpoint of further suppressing air storage, the diaphragm is preferably bent and held in a manner that its central portion bulges toward the electrode side in contact. The radius of curvature of the diaphragm held by the holding member is preferably 1000 mm or less, more preferably 500 mm or less. The lower limit of the radius of curvature is preferably 150 mm or more, more preferably 200 mm or more.

[0194] (Diaphragm)

[0195] As the separator, a separator previously used in a semi-solid battery or an all-solid battery can be appropriately selected for use. As the separator, for example, a porous membrane containing a resin material such as polyethylene, polypropylene, polybutene, polyvinyl chloride, polyethylene terephthalate, polyether sulfone, polyamide, polyimide, polyimide amide, polyaramide, polycycloolefin, nylon, polytetrafluoroethylene, etc. can be cited.

[0196] The thickness of the separator is not particularly limited, and can be 0.5 μm to 40 μm.

[0197] [Stage peeling process]

[0198] The method for manufacturing a battery of the present invention may include a step of peeling off the stage, thereby making it possible to take out the battery manufactured between the first stage and the second stage.

[0199] The method of peeling the stage is not particularly limited, and can be performed by a conventionally known method. When the stage has a suction mechanism, the peeling can be performed by eliminating the decompression state inside the stage.

[0200] [Step of thermally fusing the thermally fusing layer]

[0201] When a heat-sealing layer and a current collector are sequentially provided on the stage surface, the battery manufacturing method of the present invention may include a step of heat-sealing the heat-sealing layer on the first current collector side and the heat-sealing layer on the second current collector side of the obtained battery.

[0202] The heat-sealing method is not particularly limited, and examples thereof include a method of heating and pressing the heat-sealing portion of the heat-sealing layer.

[0203] [Step of accommodating the battery in the outer casing]

[0204] The method for producing a battery of the present invention may include a step of housing the produced battery in an exterior body.

[0205] The outer casing can be a conventionally known outer casing, for example, an outer casing made of aluminum, stainless steel, etc. The shape of the outer casing is not limited as long as it can accommodate the battery, for example, a bottomed cylindrical outer casing can be used.

[0206] The number of batteries housed in the outer casing may be one or two or more.

[0207] refer to Figure 1 to Figure 5 , an embodiment of the method for manufacturing a battery of the present invention is described. However, the method for manufacturing a battery of the present invention is not limited thereto.

[0208] like Figure 1As shown, a first stage 100 having a heat-sealing layer 10 and a first current collector 11 provided in this order on the surface, and a second stage 200 having a heat-sealing layer 20 and a second current collector 21 provided in this order on the surface are prepared.

[0209] The first stage 100 and the second stage 200 include a suction mechanism including a plurality of holes 101 and 201 on the surface and suction pipes 102 and 202 connected to the stage and a vacuum pump (not shown).

[0210] Then, if Figure 2 As shown, a positive electrode 12 is formed on the surface of a first current collector 11 to obtain a first stacked body 13 .

[0211] And, if Figure 2 As shown, a negative electrode 22 is formed on the surface of a second current collector 21 to obtain a second stacked body 23 .

[0212] like Figure 3 As shown, the first stack 13, the second stack 23 and the separator 30 are stacked to obtain a stack comprising, in sequence, a first stage 100, a battery 40 comprising a heat-sealing layer 10, a first current collector 11, a positive electrode 12, a separator 30, a negative electrode 22, a second current collector 21 and a heat-sealing layer 20, and a second stage 200.

[0213] like Figure 4 As shown, the heat-sealing layer 10 on the first current collector 11 side and the heat-sealing layer 20 on the second current collector 21 side of the battery 40 are heat-sealed.

[0214] like Figure 5 As shown, by housing the battery 40 manufactured as described above in the exterior body 50 , a battery housed in the exterior body can be obtained.

[0215] Example

[0216] Hereinafter, the above-mentioned embodiment will be described in more detail with reference to Examples, but the above-mentioned embodiment is not limited to these Examples.

[0217] (Preparation of Positive Electrode Composition)

[0218] (1) After a 0.9 mol / L LiPF6 solution (electrolyte) is mixed into a mixed solution of ethylene carbonate, propylene carbonate and diethyl carbonate, vinylene carbonate (VC) is further mixed to obtain an electrolyte solution X1.

[0219] (2) Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 2 g of a conductive aid (Ketjen Black) and 174 g of a positive electrode active material (lithium iron phosphate) were stirred at 1500 rpm (revolutions per minute, the same applies hereinafter) for 30 seconds to prepare a kneaded product Y1 (176 g).

[0220] (3) Electrolyte X1 (64 g) was added to kneaded product Y1 (176 g), and stirred at 1500 rpm for 120 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a positive electrode composition (solid content: 48 vol %).

[0221] (Preparation of Negative Electrode Composition)

[0222] (1) An electrolyte solution X1 (64 g) was prepared that was the same as the electrolyte solution used in the preparation of the positive electrode composition.

[0223] (2) Using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION), 6.5 g of the conductive additive and 152.5 g of graphite as a negative electrode active material were stirred at 900 rpm for 18 seconds to prepare a kneaded product Z1.

[0224] (3) Electrolyte X1 (64 g) was added to kneaded product Z1 (159 g), and stirred at 900 rpm for 30 seconds using a mixer (Awatori Rentaro ARE-310, manufactured by THINKY CORPORATION) to obtain a negative electrode composition (solid content: 52 vol%).

[0225] <Example 1>

[0226] As the first stage and the second stage, aluminum stages with a thickness of 30 mm were prepared.

[0227] The first stage pump and the second stage include a suction mechanism including a plurality of holes and a suction pipe connected to the stage and the vacuum pump.

[0228] A polyethylene terephthalate (PET) film (heat-welded layer) with a thickness of 12 μm, a length of 269.88 mm, and a width of 187.60 mm is disposed on the surface of the first stage. The air inside the hole of the first stage is sucked through an air suction pipe to reduce the pressure inside the hole and maintain the PET film.

[0229] A polyethylene terephthalate (PET) film (heat-welded layer) with a thickness of 12 μm, a length of 269.88 mm, and a width of 190.30 mm is disposed on the surface of the second stage. The air inside the hole of the second stage is sucked through an air suction pipe to reduce the pressure inside the hole and maintain the PET film.

[0230] The adhesive is applied to the surface of the PET film arranged on the surface of the first stage and dried to form an adhesive layer with a thickness of 8 μm. Aluminum foil (the first collector, with a thickness of 20 μm, a surface roughness Ra of 0.5 μm, and carbon coating) is laminated on the surface of the adhesive layer.

[0231] like Figure 7 As shown, the first current collector 11 includes a main body portion 11A of 203.60 mm in length and 147.60 mm in width and a label portion 11B for extracting electricity of 30.00 mm in length and 34.35 mm in width.

[0232] In addition, Figure 7 In the figure, the heat-sealed layer is indicated by reference numeral 10 .

[0233] like Figure 8 As shown, the positive electrode composition was applied to the surface of the first current collector to form a positive electrode 12 (204.60 mm long×148.60 mm wide) with a thickness of 297.3 μm, thereby obtaining a first laminate.

[0234] The adhesive is applied to the surface of the PET film arranged on the surface of the second stage and dried to form an adhesive layer with a thickness of 8 μm. Copper foil (the second collector, with a thickness of 10 μm and a surface roughness Ra of 0.55 μm) is laminated on the surface of the adhesive layer.

[0235] like Fig. 9 As shown, the second current collector 21 includes a main body portion 21A of 206.30 mm in length and 150.30 mm in width and a label portion 21B for extracting electricity of 30.00 mm in length and 34.35 mm in width.

[0236] In addition, Fig. 9 In the figure, the heat-sealed layer is indicated by reference numeral 20 .

[0237] like Fig.10 As shown, the negative electrode composition was applied to the surface of the second current collector 21 to form a negative electrode 22 having a thickness of 320.0 μm (207.30 mm in length×151.30 mm in width), thereby obtaining a second laminate.

[0238] As the separator, a polyethylene separator (thickness 20 μm) was prepared.

[0239] The end of the separator was held by a holding member (made of aluminum) and brought into contact with the positive electrode included in the first stack. Then, the separator was released from the holding member and the separator was stacked on the surface of the positive electrode.

[0240] The separator was held by a holding member in a manner that it protruded toward the positive electrode, and the radius of curvature was 350 mm.

[0241] The negative electrode of the second stack was brought into contact with a surface of the separator different from the surface in contact with the first stack, and pressed with an aluminum precision roller to obtain a stack including a first stage, a battery, and a second stage in this order.

[0242] The first stage and the second stage were peeled off and the battery was taken out.

[0243] The battery includes a heat-sealing layer, an adhesive layer, a first current collector, a positive electrode, a separator, a negative electrode, a second current collector, an adhesive layer, and a heat-sealing layer in this order.

[0244] The manufactured battery was observed with the naked eye, and as a result, no collapse of the positive electrode and the negative electrode was observed. Specifically, the battery with the first stage and the second stage peeled off was observed with the naked eye from above to confirm whether the positive electrode protruded from the first collector and the negative electrode protruded from the second collector. If protrusion was confirmed, it was determined that the positive electrode and the negative electrode collapsed.

[0245] In addition, the distance (A1) between the corner of the positive electrode of the battery and the corner of the label part of the second collector was determined, and the absolute value of the difference from the predetermined corner distance (A0: 132.4 mm) was calculated (|A1-A0|). The result was less than 0.2 mm, indicating that no offset occurred and bonding was achieved.

[0246] Explanation of symbols

[0247] 10, 20-heat-welding layer, 11-first current collector, 11A-main body, 11B-label part, 12-positive electrode, 13-first stack, 21-second current collector, 21A-main body, 21B-label part, 22-negative electrode, 23-second stack, 30-diaphragm, 40-battery, 50-outer body, 100-first stage, 101, 201-hole, 102, 202-intake pipe, 200-second stage.

[0248] The invention of Japanese Patent Application No. 2022-120967 filed on July 28, 2022 is incorporated herein by reference in its entirety. All documents, patent applications, and technical standards described in this specification are incorporated herein by reference to the same extent as if each document, patent application, and technical standard were specifically and individually described by reference.

Claims

1. A method for manufacturing a battery, comprising the following steps: A first stack is obtained by forming a positive electrode on a surface of a first current collector of a first stage having a first current collector disposed on the surface of the first stage; forming a negative electrode on a surface of a second current collector of a second stage having a second current collector disposed on the surface thereof, thereby obtaining a second stacked body; and The first stack, the second stack, and the separator are stacked to obtain a stack including the first stage, a battery, and the second stage in this order, wherein the battery includes the first current collector, the positive electrode, the separator, the negative electrode, and the second current collector.

2. The method for manufacturing a battery according to claim 1, wherein: The positive electrode and the negative electrode are formed of a composition including an active material and a conductive auxiliary agent, The solid content of the composition is 30% to 60% by volume relative to the total volume of the composition.

3. The method for manufacturing a battery according to claim 1 or 2, wherein: The first stage and the second stage have an adsorption mechanism.

4. The method for manufacturing a battery according to claim 1 or 2, wherein: A heat-sealing layer and the first current collector are sequentially provided on the surface of the first stage, and a heat-sealing layer and the second current collector are sequentially provided on the surface of the second stage.

5. The method for manufacturing a battery according to claim 1 or 2, wherein: The first stack, the second stack, and the separator are stacked by the following steps: holding the end of the diaphragm by a holding member; bringing one surface of the separator into contact with the positive electrode of the first stack or the negative electrode of the second stack; Opening the separator from the holding member and placing the separator on a surface of the positive electrode of the first stack or the negative electrode of the second stack; The positive electrode of the first stack or the negative electrode of the second stack is placed on the other surface of the separator.

Citation Information

Patent Citations

  • Continuous and semi-continuous methods for the production of semi-solid electrodes and batteries.

    JP2021530829A

  • Model generation program, model generation method, and model generation apparatus

    JP2022120967A